Carbenoxolone mitigates extensive fibrosis formation in PLP-induced EAE model and multiple sclerosis serum-exposed pericyte culture - Ucar, Ege Anil; Ozkan, Esra; Shomalizadeh, Narges; Sekerdağ-Kilic, Emine; Akpunar, Fatmanur; Sapanci, Selin; Kesibi, Judy; Ozler, Ceyda; Bilgez, Alara Su; Gursoy-Ozdemir, Yasemin (Frontiers in Cellular Neuroscience, 2024)
Introduction Multiple sclerosis (MS) is one of the most common causes of disability in young adults. Nearly, 85% of MS cases start with attacks and remissions, classified as relapsing-remitting multiple sclerosis (RRMS). With repeating attacks, MS causes brain-spinal cord atrophy and enhanced disability as disease progresses. PLP-induced EAE is one of the most established models for pathophysiology and treatment of RRMS. Recent studies demonstrated the possible role of pericytes in perivascular and intra-lesional fibrosis in PLP-induced EAE, whose importance remains elusive. Hence, we have investigated the possible role of pericytes in fibrosis formation and amelioration with a hemichannel blocker, Carbenoxolone (CBX). Methods PLP-induced experimental autoimmune encephalitis (EAE) model is used and the effect of CBX is investigated. Clinical scores were recorded and followed. Perivascular Collagen 1 and 3 accumulations were demonstrated as markers of fibrosis in the spinal cord. To delineate the role of pericytes, human brain vascular pericytes (HBVP) were incubated with the sera of MS patients to induce in-vitro MS model and the fibrosis formation was investigated. Results In the PLP induced in-vivo model, both intracerebroventricular and intraperitoneal CBX have significantly mitigated the disease progression followed by clinical scores, demyelination, and fibrosis. Moreover, CBX significantly mitigated MS-serum-induced fibrosis in the HBVP cell culture. Discussion The study demonstrated two important findings. First, CBX decreases fibrosis formation in both in-vivo and in-vitro MS models. Secondly, it improves neurological scores and decreases demyelination in the EAE model. Therefore, CBX can be potential novel therapeutic option in treating Multiple Sclerosis.